PENGARUH PELATIHAN KERJA DAN PENGHARGAAN SERTA LINGKUNGAN KERJA FISIK TERHADAP RETENSI KARYAWAN (STUDI PADA CV SUMBER ANUGRAH) - Sandy Khristian; Kusuma Chandra Kirana; Epsilandri Septyarini (Sekolah Menengah Kejuruan (SMK) Pustek, 2022)
This research was conducted to find out how the Effect of Job Training and Rewards and Physical Work Environment on Employee Retention. This research was conducted at CV Sumber Anugrah with a population of all employees of CV Sumber Anugrah with a population of 200 people and for the sample used as many as 134 people with calculations using the slovin formula. Data analysis method is quantitative analysis using purposive sampling where the purpose of this study is to describe the relationship between variables and other variables in order to test hypotheses. The sampling technique used is probability sampling, which is characterized by simple random sampling or simple random sampling is a sampling technique that gives equal probabilities to all members of a population. The results of the study are the variables of job training and rewards partially had no significant effect on employee retention, but the physical work environment variable had a significant effect on employee retention. Simultaneous test results indicate that all independent variables combined have a significant impact on CV Sumber Anugrah's employee retention.